Penguatan Identitas Visual dan Media Informasi melalui Perancangan Web Lihai Islamic Preschool - Rachmawati, Rizka; Monita, Vivi; Yudiansyah, Yudiansyah; Niswah, Nailah Khairun; Rahmah, Githa Desyana Nur (LPkM Universitas Bakrie, 2025)
Enhancing visual identity and information media is crucial for elevating the image and competitiveness of an educational institution. Lihai Islamic Preschool, which provides playgroup programs for children aged 2 to 6 years using the Ihsan, Active, and Happy approach, requires effective information media to present its vision, mission, and educational programs to the broader community. This community service initiative aims to conceptualize and develop a web that serves as a platform for information dissemination and communication. The web is crafted to meet professional standards, aesthetic appeal, and improved accessibility. The methods used in this activity include needs analysis, web structure and design, content creation (both visual and textual), and training for Lihai Islamic Preschool managers on web usage and maintenance. The result of this initiative is an interactive web that presents information comprehensively, strengthens the institution's visual identity, and enhances accessibility to information for prospective parents and the public. It is expected that this web will foster greater recognition and trust in Lihai Islamic Preschool as a model educational institution committed to nurturing early childhood character development. Additionally, this web serves as an effective communication medium between the educational institution and the community, facilitating the advancement of technology-based education that is more adaptive and contemporary.